Aronia melanocarpa (Michx.) Elliot fruit juice reveals neuroprotective effect and improves cognitive and locomotor functions of aged rats. (October 2019) - Daskalova, Elena; Delchev, Slavi; Topolov, Mariyan; Dimitrova, Stela; Uzunova, Yordanka; Valcheva-Kuzmanova, Stefka; Kratchanova, Maria; Vladimirova-Kitova, Lyudmila; Denev, Petko
Abstract: The aim of the study was to investigate the effect of polyphenol-rich Aronia melanocarpa (Michx.) Elliot juice (AMJ) on learning ability and memory, and brain morphology of aged rats. A model of healthy male Wistar rats (24 months of age) divided in 2 groups was used: AMJ group supplemented orally with AMJ (10 mL/kg for 105 days) and old control (CO) group without supplementation. Activity cage test showed that AMJ supplemented rats increased the number of vertical movements compared with old controls (p < 0.05). In active avoidance test, supplemented rats increased the number of avoidances on 3rd, 4th and 5th days of learning session, compared with the respective day of old controls (p < 0.05). AMJ supplementation did not affect the mean neuronal number in the dentate gyrus but significantly increased the density of nerve fibers in the perforant path of the hippocampus (p < 0.05). AMJ supplementation increased acetylcholinesterase activity in hippocampus, which is a marker of improved functional activity of the cholinergic neurons. These results indicate that AMJ induced ameliorating changes in the ability of old rats to learn tasks and improved their locomotor functions. AMJ showed a neuroprotective effect by increasing the density of nerve fibers in the hippocampal perforant pathway. Highlights: Aronia melanocarpa juice (AMJ) is very rich in polyphenols and anthocyanins. AMJ improves locomotor functions and short-term memory of aged rats. AMJ increases the density of nerve fibers in the hippocampal perforant pathway. AMJ increases the functional activity of cholinergic neurons. AMJ has a neuroprotective effect in aged rats.